Pendekatan Integratif terhadap Faktor yang Mempengaruhi Intensi Buruh untuk Mengikuti Aksi Kolektif - Soeharso, Silverius Yoseph (Makara Human Behavior Studies in Asia, 2009)
This research attempts to build a structural model based on an integrative approach to explain labor intention to participate in collective action. This research is relevant as most of the existing theories and approaches explain the collective action phenomena partially. The main objective of this research is to analyze the integrative approach of psychological social psychology (individual factors), sociological social psychology (inter-group relation factors) and social constructionism (societal factor) in explaining labor intention to participate in collective action, such as demonstrations and labor strikes. This integrative approach research tested a theoretically derived pattern of specific relationship between individual level of analysis, inter-group relation and societal or ideological level of analysis where each level of analysis was represented by one or more theories. The research model proposes three exogenous latent variables namely: social representation, organizational commitment and union commitment, and four endogenous latent variables that are: social identity, relative deprivation, expectancy-value motives and intention to participate in collective action. These research findings proved that an integrative approach model which was represented by expectancy-value motives (individual level), both relative deprivation and social identity (inter-group level) and social representation (societal level) explain the labor intention participating in collective action was significant in non participant sample. On the other hand, in participant sample there were only two factors namely inter-group relation and societal context which explain the emerging of the labor intention participating in collective action.